2007
DOI: 10.1161/circulationaha.107.693739
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Correlates of Late Drug-Eluting Stent Thrombosis

Abstract: Background-Late stent thrombosis (LST) after Cypher and Taxus drug-eluting stent placement has emerged as a major concern. Although the clinical predictors of LST have been reported, specific morphological and histological correlates of LST remain unknown. Methods and Results-From a registry totaling 81 human autopsies of drug-eluting stents, 46 (62 lesions) had a drug-eluting stent implanted Ͼ30 days. We identified 28 lesions with thrombus and compared those with 34 of similar duration without thrombosis usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
376
2
12

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 1,188 publications
(396 citation statements)
references
References 22 publications
(22 reference statements)
6
376
2
12
Order By: Relevance
“…As the previous studies reported, reendothelialization following stent implantation is very important to prevent stent thrombosis3, 4 because the exposure of stent strut surfaces to the bloodstream may result in thrombus formation 16. Synergy showed the fastest neointimal coverage in atherosclerotic rabbits among the DESs investigated.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…As the previous studies reported, reendothelialization following stent implantation is very important to prevent stent thrombosis3, 4 because the exposure of stent strut surfaces to the bloodstream may result in thrombus formation 16. Synergy showed the fastest neointimal coverage in atherosclerotic rabbits among the DESs investigated.…”
Section: Discussionmentioning
confidence: 92%
“…All animals were premedicated with oral aspirin (40 mg/day) 2 days before the procedure 4, 16, 17. Rabbits were anesthetized with 2.5% isoflurane via facemask.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4,16,17 Indeed, Finn and colleagues reported incomplete neointimal coverage of stent struts as the most important morphometric predictor of LST. 4 However, the unexplained variation was high (1-r 2 =81.5%), and the results may not be representative of patients who receive DES and survive.…”
Section: Pathology Of Stent Thrombosismentioning
confidence: 99%
“…3 This concept is based on clinical autopsy studies and clinical intracoronary angioscopy studies. 4,5 However we feel this concept is still open to debate. Our hypothesis is that delayed re-endothelialisation alone is not adequate to explain LST.…”
mentioning
confidence: 99%